STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI PESERTA DIDIK PADA MASA NEW NORMAL COVID-19 DI SMP NEGERI 6 PALEMBANG - Reka Maulia; Zuhdiyah Zuhdiyah; Fitri Ovianti (PAI RAFAH, 2022)
The purpose of this study to determine the teaching strategies used by Islamic Religious Education teachers in inscreasing students’ learning motivation during the New Normal Covid-19 Period, and the implications of the strategies used by Islamic Religious Education teachers on students’ learning motivation in the New Normal Covid-19 at SMP Negeri 6 Palembang.This type of research is a field research with a descriptive qualitative approach. Data collection techniques in this study were obtained through observation, interviews, and documentation, while the informants were Islamic Religious Education teachers, school principals, and VIII grade students of SMP Negeri 6 Palembang.After conducting research at SMP Negeri 6 Palembang, the results obtained that the learning implementation system applied by schools during the current New Normal Covid-19 period was the Face-to-Face Learning System (PTM). The teaching strategies used by Islamic Religion Education teachers during the implementation of learning in the New Normal are Expository and Inquiry Learning Strategies, these strategies were chosen to adjust students’ conditions so that they easily understand the material explained by teacher, and help increase the enthysiasm of student in participating, in teaching, and learning activities.So that it can increase students’ learning motivation during the Covid-19 New Normal Period. Meanwhile, the implication or impact of the strategy used by the teacher on the learning motivation of students is that it greatly impacts on increasing the motivation of students when participating in the learning process activities, it is because students easily understand the material explained and the way the teacher applies learning strategies is able to increase student learning motivation. in participating in teaching and learning activities.